第53次日本南極地域観測隊 東京海洋大学研究練習船「海鷹丸」（KARE-15; UM-11-07）活動報告 - 茂木, 正人; Moteki, Masato (2015)
P(論文) 2011/2012年夏シーズンに，東京海洋大学研究練習船「海鷹丸」の海洋研究航海が，南大洋インド洋区で行われた．この航海では東京海洋大学の共同研究5課題が行われた．このうち，以下の2課題が南極地域観測第Ⅷ期計画（第52?57次隊）関連研究であった．すなわち，一つは重点研究観測「南極から探る地球温暖化」のサブテーマの一つである「南極海生態系の応答を通して探る地球環境変動」で，もう一つは一般研究観測の「プランクトン群集組成の変動と環境変動との関係に関する研究」であった．これら南極観測事業関連研究のほか，東京海洋大学・国立極地研究所との共同研究である「南大洋の環境変動と生態系変動」，独立行政法人海洋研究開発機構（JAMSTEC）との共同研究「時系列観測による南大洋の大気・海洋環境変動の研究（南大洋ブイの開発）」，北海道大学との共同研究「南極底層水の動態に関する研究」も同時に実施された．「海鷹丸」は平成23年12月27日，フリーマントルを出港後，東経110度及び140度の海氷縁に及ぶ海域の観測を行い，平成24年2月1日，ホバート港へ寄港した．この間，プランクトン群集の分布を調べるため各種ネットによる曳網が行われたほか，物理観測，化学成分観測が行われた．また，昨シーズンに設置した長期係留系を回収した．また，「しらせ」から放流された漂流ブイ2系統を回収した．さらに，JAMSTECのm-TRITON ブイを設置した．こうした観測のほか，翼足類を用いた酸性化実験が船上で行われた． The training vessel Umitaka-maru of the Tokyo University of Marine Science and Technology (TUMSAT) undertook a marine science cruise in the Indian sector of the Southern Ocean during the 2011/2012 austral summer. During the cruise, TUMSAT conducted five different collaborative research projects. These included two phase-VIII Japanese Antarctic Research Expedition (JARE-52 to -57) projects: "Responses of Antarctic Marine Ecosystems to Global Environmental Changes with Carbonate Systems", which is the sub-theme of the prioritized research project "Exploring Global Warming from Antarctica"; and the ordinary research project "Studies on Plankton Community Structure and Environment Parameters in the Southern Ocean". The other three collaborative research projects were those undertaken in conjunction with (1) the National Institute of Polar Research, entitled "Environment and Ecosystem Changes in the Southern Ocean"; (2) the Japan Agency for Marine-Earth Science and Technology (JAMSTEC), entitled "Deployment of the Southern Ocean Buoy" and (3) with Hokkaido University, entitled ＂Studies on Dynamics of Antarctic Bottom Water＂. The Umitaka-maru departed from Fremantle, Australia, on 27 December 2011, sailed to the study area around the marginal sea ice zone (mainly along 110°E and 140°E), and returned to Hobart, Australia, on 1 February 2012. The participants performed various ...